2010
DOI: 10.1097/scs.0b013e3181f43f43
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Properties of a Maxillofacial Silicone Elastomer Incorporating a ZnO Additive

Abstract: The main objective of the current study was to investigate the dynamic mechanical properties of a room-temperature vulcanizing silicone incorporating different fractions of zinc oxide (ZnO) after indoor and outdoor photoaging. Forty-eight samples were produced by adding different amounts of ZnO into a commercial maxillofacial silicone (EPISIL-E). The samples were divided into 4 groups containing 0.0, 0.2, 0.5, and 1 wt% ZnO additive, respectively. Samples were exposed to sunlight (subgroup 2), ultraviolet (sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…44 One important factor affecting the thermomechanical properties of maxillofacial silicones is the percentage of cross-linking and crystallinity as it has been proven by DMA. 38,45 The decrement of Tg values could be associated with decreased density of cross-links after disinfection procedures or chain scissions due to continuous polymerization of elastomer or absorption phenomena. Goiato et al 11,24 have reported possible increment in cross-linking density after disinfecting silicone maxillofacial elastomers using neutral soap and effervescent denture cleanser tablets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 One important factor affecting the thermomechanical properties of maxillofacial silicones is the percentage of cross-linking and crystallinity as it has been proven by DMA. 38,45 The decrement of Tg values could be associated with decreased density of cross-links after disinfection procedures or chain scissions due to continuous polymerization of elastomer or absorption phenomena. Goiato et al 11,24 have reported possible increment in cross-linking density after disinfecting silicone maxillofacial elastomers using neutral soap and effervescent denture cleanser tablets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of solar aging and elastomer composition could cause significant alterations on all dynamic properties. 38 Thus, the DMA proved to be a rapid, reliable, and convenient method for the determination of viscoelastic properties of maxillofacial materials. 29 Relationships between physical structure and mechanical properties allow the understanding of dynamic mechanical behavior of elastomers.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Zinc oxide (Mouzakis et al, 2010): It is also known as flowers of zinc and zinc white. It is an inorganic compound, and occurs naturally as the mineral zincite but mostly zinc oxide is produced synthetically.…”
Section: Additives In Cream and Pastementioning
confidence: 99%
“…A work published in 2010 showed that the combination of indoor and outdoor photo‐aging and different fractions of zinc oxide had significant effect on all silicone dynamic properties. MDX 4‐4210 silicone containing opacifiers showed greater hardness after 1008 hours of accelerated aging independent of disinfectant type …”
Section: Resultsmentioning
confidence: 99%